CRIMINALIZING POLICY OF SEXUAL HARASSMENT - Lect. Dr. Nawras Ahmed Kazem Al Mousawi (Scholar Express Journals, 2022)
Harassment is a social, psychological, and legal issue that infringes on the right to privacy, the protection of one's body, and dignity, as well as putting one's psychological and social safety at risk. It is often misunderstood for its privacy as it represents one of the taboos that should not be addressed in Arab societies in particular. Previously, people were afraid to use that term, especially when it was connected with the word sexual. However, with the increase in this dangerous phenomenon at the present time, it has become necessary to delve into its merits. It cannot be ignored or pretend that it does not exist. Moreover, sexual harassment was not mentioned by the Iraqi legislator in the amended Penal Code, except for what was stated in Article (402), which referred to the criminalization of exposure to a female in the public place with words, actions or facial gestures in particular which cause the woman’s modesty under harassment. This punishment for such an act is as light as air when compared to this dangerous act.
Keywords: Politics; Criminality; Harassment; Sexual